The Impact of Learning Styles in Teaching English - Axmedjanova Farida Djavairovna (International Journal on Integrated Education, 2022)
Learning style is one of the main factors that determines how students learn English and has a signiﬁcant inﬂuence on students’ learning strategy selection, which further affects their learning outcomes.